Cryoelectron microscopy of λ phage DNA condensates in vitreous ice: The fine structure of DNA toroids - Hud, Nicholas V. (The National Academy of Sciences, 2001)
DNA toroids produced by the condensation of λ phage DNA with hexammine cobalt (III) have been investigated by cryoelectron microscopy. Image resolution obtained by this technique has allowed unprecedented views of DNA packing within toroidal condensates. Toroids oriented coplanar with the microscope image plane exhibit circular fringes with a repeat spacing of 2.4 nm. For some toroids these fringes are observed around almost the entire circumference of the toroid. However, for most toroids well-defined fringes are limited to less than one-third of the total toroid circumference. Some toroids oriented perpendicular to the image plane reveal DNA polymers organized in a hexagonal close-packed lattice; however, for other toroids alternative packing arrangements are observed. To aid interpretation of electron micrographs, three-dimensional model toroids were generated with perfect hexagonal DNA packing throughout, as well as more physically realistic models that contain crossover points between DNA loops. Simulated transmission electron microscopy images of these model toroids in different orientations faithfully reproduce most features observed in cryoelectron micrographs of actual toroids.